A DIVERSIDADE RELIGIOSA NO ESPAÇO ESCOLAR ADVENTISTA DO ABCD PAULISTA - MARQUES, IGOR EMANUEL DE SOUZA (2015)
Against the backdrop of the denominational status of network Adventist education present in a remarkable way in the school space and the intense religious diversity students, this research analyzes the relationship of possible tensions between the denominational school status and religious diversity present. It takes into account the process of modernity causing significant change in education, in religion and in the form of the two institutes relate to each other. It took into account the socio-economic and religious profile of the students and how is the reception of religious education in Adventist school space, including students who declare themselves Adventists. The area chosen for this research was the Adventist schools located in the ABCD Paulista context, which offer high school. These school units are located in the cities of Diadema, Santo Andre and Sao Caetano do Sul, cities located in the same micro region, but with different socioeconomic realities.